Effect of functional monomers on the binding properties of molecularly imprinted polymers (MIPs) for selective recognition of dexamethasone - Adauto, Anais; Khan, Sabir [UNESP]; Vega-Chacón, Jaime; Sotomayor, Maria D. P. T. [UNESP]; Picasso, Gino (Wiley, 2025)
This study examined the feasibility of removing dexamethasone (DEX) from aqueous solutions using molecularly imprinted polymers (MIPs). The binding energy, used to evaluate the affinity between imprinted molecule and functional monomer, was calculated for DEX using molecular simulation via the density functional theory method. From this approach, three different functional monomers were tested: methacrylic acid, N-(Hydroxymethyl) acrylamide, and 2-hydroxyethyl methacrylate designated as MIP-DEX1, MIP-DEX2, MIP-DEX3, respectively. All of them were prepared by the precipitation polymerization method, with trimethylolpropane trimethacrylate used as the crosslinker. Moreover, the kinetics of adsorption and adsorption isotherms were evaluated using different models to assess the adsorption mechanisms of DEX on polymers. The results showed that equilibrium between the polymer and DEX is reached at 180 min, with a maximum adsorption capacity of 117.27 mg g−1 for sample MIP-DEX3. The kinetic studies indicated that the adsorption of DEX on the polymers fits very well with the pseudo-second-order kinetic model. Equilibrium data were best described by the Freundlich model, suggesting that the sorption process occurs on a heterogeneous surface of the polymer cavities. The thermodynamic study confirms the role of selectivity cavities, exhibited in the sample MIP-DEX3. Reusability tests and application on real samples suggest that the synthesized polymers are promising adsorbents. Highlights: The functional monomer was chosen using a semiempirical computational simulation. Three monomers were tested to study their influence on dexamethasone recognition. The molecularly imprinted polymers (MIPs) prepared from 2-hydroxyethyl methacrylate achieved the maximum analyte adsorption. Our MIP exhibited a selectivity constant of 41.11 in the presence of cortisone. The prepared MIP was successfully reused and tested for dexamethasone in real water samples.
Keywords: adsorption; dexamethasone; functional monomer; molecularly imprinted polymers (MIPs)